BIASES IN DECISION MAKING (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
Every day we make decisions, of all kind, under uncertainty. Decision-making a process that involves the evaluation of different variables. There are formal tools that help us to decide, but these tools are affected by the "biases" of our mind. The previous information that we have at the time of deciding helps us to solve, but the one who decides cannot have the absolute certainty, since our brain can distort the information.From the cognitive perspective, between the environmental stimuli and the decisions of the people, finds an element that processes the information, that interprets the stimuli and chooses the answer, the psychology has been exploring the modalities and the effects of that processing on the taking of decisions. Its main contribution to this knowledge is the detection of cognitive biases, of inevitable distortions in the way of evaluating options and choosing. (Laca Arocena, 2012)In general, making a decision is the act of choosing or selecting. It is a mental process in which it is possible to identify the actions that will be taken to solve a problem or a disjunctive to achieve an objective. It implies, then, having the freedom to choose within a series of possibilities. This action involves an intentionality, which comprises a series of values. In all types of organizations, decisions are made between the members that compose it and that are immersed in it. The decision-making process means a habit, or in an economic reductionist sense, an economy of efforts. The actions as they become a routine, are repeated and thus have a meaning that is gradually anchored in knowledge. (Vidal, 2012)
Keywords: decision theory; bias; heuristic